Task-Based Language Teaching Integrated with Digital Literacy in Improving Pre-Service Indonesian Language Learners’ Communicative Competences - Ayu Puspita Indah Sari; Yeni Ernawati; Enny Hidajati (Universitas Pendidikan Mandalika, 2026)
This study investigates whether an integrated Task-Based Language Teaching (TBLT) and digital literacy sequence enhances pre-service Indonesian Language (PIL) teachers’ communicative competences and how they perceive and adapt the model under classroom constraints. Using an explanatory sequential mixed-methods design, researchers first conducted a quantitative pre–post evaluation with 25 PIL participants enrolled in an Indonesian Language Education program. Communicative performance was assessed through parallel speaking, writing, and multimodal tasks rated on four analytic dimensions—linguistic, pragmatic, discourse, and strategic—supplemented by a multimodal criterion. Descriptive statistics indicated overall gains to a proficient band, with discourse and strategic competences displaying the highest central tendency and the narrowest dispersion. Linguistic and pragmatic competences improved but showed wider between-learner variance, suggesting uneven consolidation of affixes, pronouns, particles, and register-appropriate choices. The qualitative follow-up (observations, interviews) explained these patterns: the pre-task → task → post-task cycle, combined with purpose-bound digital supports, stabilized interactional routines, made discourse organization visible, and prompted targeted focus-on-form. Participants adapted to assessment pressure, class size, and technology access through role rotation, offline-first drafting, low-bandwidth alternatives (audio + transcript), and a standardized “core trio” of tools, which reduced cognitive load and widened equitable participation.